2020
DOI: 10.3390/app10228262
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Mercury Removal at Ultralow Metal Concentrations by Cysteine Functionalized Carbon-Coated Magnetite

Abstract: This work reports the preparation and utility of cysteine-functionalized carbon-coated Fe3O4 materials (Cys-C@Fe3O4) as efficient sorbents for remediation of Hg(II)-contaminated water. Efficient removal (90%) of Hg(II) from 1000 ppb aqueous solutions is possible, at very low Cys-C@Fe3O4 sorbent loadings (0.01 g sorbent per liter of Hg(II) solution). At low metal concentrations (5–100 ppb Hg(II)), where adsorption is typically slow, Hg(II) removal efficiencies of 94–99.4% were achievable, resulting in final Hg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Moreover, results of kinetic studies also suggest that adsorption kinetics were best described by the PSO kinetic model, with a high correlation coefficient ( R 2 > 0.99) and the lowest χ 2 , for single adsorption of pesticides on the NFMBC via prevalent chemisorption processes for all pesticides studied. 61 These results are consistent with previous studies on adsorption of pesticides by biochar sorbents, in which the pseudo-second-order model has a better fit to the experimental data than others. 52 , 57 , 62 Additionally, the higher values of α relative to β in the adsorption process from the Elovich model indicate that the initial rate of adsorption is higher than the desorption rate, 63 implying that NFMBC is an effective sorbent for aqueous pesticide removal.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, results of kinetic studies also suggest that adsorption kinetics were best described by the PSO kinetic model, with a high correlation coefficient ( R 2 > 0.99) and the lowest χ 2 , for single adsorption of pesticides on the NFMBC via prevalent chemisorption processes for all pesticides studied. 61 These results are consistent with previous studies on adsorption of pesticides by biochar sorbents, in which the pseudo-second-order model has a better fit to the experimental data than others. 52 , 57 , 62 Additionally, the higher values of α relative to β in the adsorption process from the Elovich model indicate that the initial rate of adsorption is higher than the desorption rate, 63 implying that NFMBC is an effective sorbent for aqueous pesticide removal.…”
Section: Resultssupporting
confidence: 92%
“…This observation agrees with data from other studies investigating the interaction of Hg 2+ with Fe 3 O 4 that reported no or negligible binding. 36,77–81…”
Section: Resultsmentioning
confidence: 99%
“…This observation agrees with data from other studies investigating the interaction of Hg 2+ with Fe 3 O 4 that reported no or negligible binding. 36,[77][78][79][80][81] 3.6. Binding coordination studies with 13 C and 15 N NMR A detailed study of the binding constraints of Hg 2+ with the material was analyzed with 13 C and 15 N. The results revealed that Hg 2+ binds to the heptazine structure of g-CN and not the magnetite particles (Fig.…”
Section: Investigation Of G-cn and M-g-cn Surface Area And Binding Pr...mentioning
confidence: 99%
“…With a constant ratio of m P / m Hg2+ and the initial concentration [Hg 2+ ] 0 range of 5 to 100 mg/L, the removal efficiencies of hb ‐P 1 were generally measured to be above 99.92%, and the remaining [Hg 2+ ] could be decreased to as low as 0.10 μg/L, which was below the limit of drinking water standards of WHO (6 μg/L), U.S. (2 μg/L), China and EU (1 μg/L) (Figure 5 and Table S1). [ 63‐64 ] Similarly, hb ‐P 5 and hb ‐P 6 also showed high removal efficiency, and slightly decreased efficiency with low [Hg 2+ ] 0 compared with hb ‐P 1 , maybe due to the relatively flexible structures compared with hb ‐P 1 .…”
Section: Resultsmentioning
confidence: 99%